2019
DOI: 10.3390/resources8020107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ambient Parameters on the Temperature Distribution of Photovoltaic (PV) Modules

Abstract: This paper pivots around the influence of thermal parameters on the temperature distribution of a (PV) module. The solar irradiance, ambient temperature, and heat transfer coefficient were examined for four differently manufactured solar modules. A finite element analysis of the solar system was carried out to simulate the prevailing thermal conditions. It was determined through analysis that the heat transfer coefficient had a significant effect on the boundaries of the PV modules. The temperature gradient wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Based on the configuration of the photovoltaic array, the shading effect on the specific PV system can be studied. An efficient and unifying approach to investigating and determining the behavior of PV modules, a maximum power point tracking system can be used together with a specific algorithm such as fuzzy logic, disturbance and observation, buck converter, incremental inductance, i.e., [39][40][41][42][43][44].…”
Section: Knowledge and State Of The Artmentioning
confidence: 99%
“…Based on the configuration of the photovoltaic array, the shading effect on the specific PV system can be studied. An efficient and unifying approach to investigating and determining the behavior of PV modules, a maximum power point tracking system can be used together with a specific algorithm such as fuzzy logic, disturbance and observation, buck converter, incremental inductance, i.e., [39][40][41][42][43][44].…”
Section: Knowledge and State Of The Artmentioning
confidence: 99%
“…Both the electrical efficiency and, hence, the power output of a PV module depend linearly on the operating temperature decreasing. It has been reported that PV module power output decreases by 0.4 -0.5% for 1°C increase in temperature above the standard operating temperature, depending on the temperature coefficient of the power of the module [17].…”
Section: Considered Factors For Estimation Of Solar Power Production a Global Horizontal Irradiance (Ghi)mentioning
confidence: 99%
“…However, under direct sunlight, the cell temperature becomes around 30 • C higher than the ambient temperature. PV panel efficiency is affected negatively by temperature increase [59,60]. It is obvious from the simulation results that the variation of the annual average ambient temperature from −20% to +20% of the basic value results in reducing the renewable fraction from 55.8% to 52.7%, and this leads to an increase in the NPC from USD 33,206 to USD 34,255.…”
mentioning
confidence: 93%